Menentukan Koefisien Transfer Massa dan Diffusivitas Efektif dari Proses Dekolorisasi Zat Warna - Primata Mardina (INFO-TEKNIK, 2007)
Dyes are used in various sectors like textile, paper and dyeing industries which discharge waste colored dye liquid. Solid-liquid adsorption principal has been used to decolorize it. The experiment has used granular activated carbon as adsorbent. The experiment’s purpose is determining mass transfer coefficient (Kc) and effective diffusivity (De) as adsorption equipment design parameter.The dye adsorption follows the Langmuir equilibrium equation. The effects of system variables are initial concentration and impeller rotated velocity. The value of Kc of dye at 100 ppm, 80 ppm, 60 ppm, 40 ppm and 20 ppm were found to be 5.209 x 10-4 g/cm2/minute, 5.17 x 10-4 g/cm2/minute, 5.151 x 10-4 g/cm2/minute, 5.163 x 10-4 g/cm2/minute and 5.85 x 10-4 g/cm2/minute. The value of De at 100 ppm, 80 ppm, 60 ppm, 40 ppm and 20 ppm were found to be 3.249 x 10-4 cm2/minute, 3.127 x 10-4 cm2/minute, 3.107 x 10-4 cm2/minute, 3.004 x 10-4 cm2/minute and 3.524 x 10-4 cm2/minute. The value of Kc of dye at 400 rpm, 500 rpm and 600 rpm were found to be 5.999 x 10-4 g/cm2/minute, 5.85 x 10-4 g/cm2/minute and 8.369 x 10-4 g/cm2/minute. The value of De at 400 rpm, 500 rpm and 600 rpm were found to be 3.978 x 10-4 cm2/minute, 3.524 x 10-4 cm2/minute and 3.995 x 10-4 cm2/minute. The experiment result is approximated with mathematical equation This equation prevails in Reynolds Number 3000 until 5600 with average relative error 9.3114 %.